Cognitive decline among individuals with history of mild symptomatic SARS‐CoV‐2 infection: A longitudinal prospective study nested to a population cohort. (1st March 2021) - Del Brutto, Oscar H.; Wu, Shasha; Mera, Robertino M.; Costa, Aldo F.; Recalde, Bettsy Y.; Issa, Naoum P.
Abstract: Background and purpose: Neurological complications of SARS‐CoV‐2 infection are noticed among critically ill patients soon after disease onset. Information on delayed neurological sequelae of SARS‐CoV‐2 infection is nil. Following a longitudinal study design, the occurrence of cognitive decline among individuals with a history of mild symptomatic SARS‐CoV‐2 infection was assessed. Methods: Stroke‐ and seizure‐free Atahualpa residents aged ≥40 years, who had pre‐pandemic cognitive assessments as well as normal brain magnetic resonance imaging and electroencephalogram recordings, underwent repeated evaluations 6 months after a SARS‐CoV‐2 outbreak infection in Atahualpa. Patients requiring oxygen therapy, hospitalization, and those who had initial neurological manifestations were excluded. Cognitive decline was defined as a reduction in the Montreal Cognitive Assessment (MoCA) score between the post‐pandemic and pre‐pandemic assessments that was ≥4 points greater than the reduction observed between two pre‐pandemic MoCAs. The relationship between SARS‐CoV‐2 infection and cognitive decline was assessed by fitting logistic mixed models for longitudinal data as well as exposure‐effect models. Results: Of 93 included individuals (mean age 62.6 ± 11 years), 52 (56%) had a history of mild symptomatic SARS‐CoV‐2 infection. Post‐pandemic MoCA decay was worse in seropositive individuals. Cognitive decline was recognized in 11/52 (21%) seropositive and 1/41 (2%) seronegative individuals. In multivariate analyses, the odds for developing cognitive decline were 18.1 times higher among SARS‐CoV‐2 seropositive individuals (95% confidence interval 1.75–188; p = 0.015). Exposure‐effect models confirmed this association ( β = 0.24; 95% confidence interval 0.07–0.41; p = 0.006). Conclusions: This study provides evidence of cognitive decline among individuals with mild symptomatic SARS‐CoV‐2 infection. The pathogenesis of this complication remains unknown. Abstract : This population‐based longitudinal prospective cohort study, conducted in a selected population of community‐dwelling middle‐aged and older adults living in a rural village severely struck by the SARS‐CoV‐2 pandemic, demonstrates that individuals with a history of mild symptomatic SARS‐CoV‐2 infections have more than 18 times the odds of developing late substantial cognitive decline than those without clinical and serological evidence of the infection.